Retraining dorsal visual pathways improves cognitive skills and executive control networks following mild traumatic brain injury - Lawton, Teri; Shelley-Tremblay, John; Lee, Roland R.; Huang, Ming-Xiong (Frontiers in Human Neuroscience, 2025)
Background and objectivesMild traumatic brain injury (mTBI) frequently results in persistent cognitive deficits with limited evidence-based rehabilitation options. Visual timing deficits, potentially linked to dorsal visual pathway dysfunction, represent a promising therapeutic target. This study examined whether a novel intervention targeting dorsal visual pathways (PATH) demonstrates superior efficacy compared to conventional cognitive therapies targeting ventral pathway deficits or working memory impairments.MethodsTwenty-four participants (aged 23–62 years) with mTBI were randomized to receive one of three interventions over 12 weeks: (1) PATH training targeting dorsal visual pathway function, (2) Orientation Discrimination (OD) targeting ventral pathway pattern discrimination, both of these 20-min interventions followed by 10-min of digit memory exercises, or (3) ReCollect, working memory training. Each intervention consisted of 36 sessions (30 min each, three times weekly). Primary outcome was visual working memory (VWM) performance; secondary outcomes included processing speed, reading speed, auditory working memory, selective attention, and cognitive flexibility assessed via standardized neuropsychological measures. Magnetoencephalography (MEG) recordings during resting state and an N-Back task provided neurophysiological validation.ResultsPATH training yielded significantly greater VWM improvements (49%) compared to ReCollect (13%) and OD (8%) interventions. Repeated-measures ANOVA confirmed superior efficacy of dorsal pathway training (significant at p = 0.011). Similar gains for PATH training were also found for processing speed, reading speed, and cognitive flexibility, especially when compared to the OD group, revealing importance of strengthening the dorsal stream before digit memory exercises. MEG analysis revealed PATH-specific activation in not only bilateral dorsolateral prefrontal cortex, anterior cingulate cortex, posterior parietal cortex, superior occipital gyri, but also the left anterior temporal lobe and hippocampus, primary motor cortex, and the cerebellum, as well as lower gamma-band noise, suggesting enhanced neural timing, attention, working memory, memory consolidation and retrieval mechanisms beyond the targeted dorsal pathways.ConclusionDorsal visual pathway retraining followed by targeted working memory exercises demonstrates superior therapeutic efficacy for cognitive rehabilitation following mTBI compared to conventional approaches. The intervention promotes beneficial neuroplasticity extending to memory-related brain regions, supporting its potential as a targeted, mechanistically-informed therapy for post-concussive cognitive deficits.